The brains behind great ad campaigns : creative collaboration between copywriters and art directors - Berman, Margo, 1947- 4 0 16; 1958- Blakeman, Robyn; 5 (Lanham, Md. : Rowman & Littlefield Publishers, 2009)
Discusses the collaborative advertising process, covering topics such as layout style, storytelling, strategic verbal and visual approaches, brainstorming, and more, with examples, illustrations, and advice on the fundamentals of an effective ad campaign.
Includes bibliographical references and index.
Adult;Adult
Keywords: 2 -- 0; 6; Advertising campaigns.;Brand name products.;Advertising.;Brand name products; 20; 2